Synthesis and in vitro inhibition effect test of nanochitosan-Cu againts Fusarium oxysporum and Colletotrichum - Sri Wahyuni (Menara Perkebunan, 2020)
Wilt and anthracnose are diseases on chili that cause substantial losses and even crop failure. Control of the diseases is generally carried out using chemical pesticides which are environmentally harmful. Therefore, the development of nanoparticles, such as nanochitosan-Cu, can be an environmentally friendly solution in controlling chili disease. The current technology in developing nanochitosan-Cu is green synthesis, which uses an effective reducing agent but non-toxic for plants and the environment. However, the process requires sonication, which is difficult to be adapted for scale-up production. This research aimed to synthesize and determine the formulation of nanochitosan –Cuusing magnetic stirrer method without sonication, and also to evaluate the antifungal ability of nanochitosan-Cu againstFusarium oxysporum and Colletotrichum capcisi causing wilt and anthracnose disease, respectively. Synthesis of nanochitosan-Cu was carried out at 50°C and 400 rpm of speed. Characterizations of nanochitosan-Cu were analyzed using SEM-EDX and PSA. In vitro antifungal activity test was carried out by food poisoning method.The results showed that the synthesis of nanochitosan-Cu using ionic gelation method can be carried out without sonication process, and produce round shape nanoparticles with 183.7 nm of diameter. The nanochitosan-Cu was effective against F. oxysporum and C. capsici, at a concentration of 100 ppm. It inhibited the growth of F. oxysporum and C. capsici by 100% and 92.38%, respectively.